Agglomeration of Ag and TiO2 nanoparticles in surface and wastewater: Role of calcium ions and of organic carbon fractions. (September 2015) - Topuz, Emel; Traber, Jacqueline; Sigg, Laura; Talinli, Ilhan
Abstract: This study aims to investigate factors leading to agglomeration of citrate coated silver (AgNP-Cit), polyvinylpyrrolidone coated AgNPPVP and titanium dioxide (TiO2 ) nanoparticles in surface waters and wastewater. ENPs (1 mg/L) were spiked to unfiltered, filtered, ultrafiltered (<10 kDa and <1 kDa) samples. Z-average particle sizes were measured after 1 h, 1 day and 1 week. AgNP-PVP was stable in all fractions of the samples and kept their original size around 60 nm over 1 week. Agglomeration of AgNP-Cit and TiO2 was positively correlated with Ca 2+ concentration, but dissolved organic carbon concentrations > 2 mg/L contributed to stabilizing these NP. Moreover, agglomeration of AgNP-Cit in the various organic matter fractions showed that high molecular weight organic compounds such as biopolymers provide stabilization in natural water. A generalized scheme for the agglomeration behavior of AgNP-Cit, AgNP-PVP and TiO2 in natural waters was proposed based on their relation with Ca 2+, Mg 2+ and DOC concentration. Graphical abstract: Highlights: Agglomeration of AgNP-Cit was positively correlated with Ca 2+ concentration. DOC > 2 mg/L contributes to stabilizing AgNP-Cit and TiO2 . High molecular weight biopolymers provide stabilization in natural water. Z-average sizes of AgNP-Cit in filtered samples were higher than in unfiltered ones. AgNP-PVP is stable in surface and wastewater over 1 week. Abstract : Agglomeration of ENP in natural waters and wastewater was mostly dependent on the calcium ion and dissolved organic carbon concentrations.